The decisions of economic authorities (policy mix) and the financial system stability in Poland - Stawska, Joanna (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
The lack of financial stability is a factor that favors the financial crises understood as a disturbance in the functioning of financial markets. In addition, the financial crisis may lead to financial instability. Financial crises highlight the importance of financial stability in the economy. In this context, coordination of monetary and fiscal policy becomes important in periods of stability in the financial markets, however, in exceptional circumstances, e.g. crisis, takes on special significance. This article aims to analyze the decisions made by economic authorities in Poland and their consequences for the stability of the financial system, especially in the exceptional circumstances of the financial crisis. To achieve this objective, the following methods were used: a literature review, statistical research methods and graphical presentation of phenomena. Certainly, monetary and fiscal policies together influence the shaping of balance in the economy of the country concerned. Hence, this topic is important at least because of fact that the choice of the optimal combination of monetary and fiscal policy is difficult because of the diversity of the objectives and preferences of economic authorities. It seems that the financial crisis and its aftermath may have contributed to the cooperation of the central bank and the government, which in turn could have a positive impact on the level of financial stability in Poland.